Maternal and Fetal Outcome in Gestational Diabetes Mellitus - Akhter, Shahnaz; Karim, Md Rizwanul (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Gestational diabetes mellitus (GDM) is a problem of growing interests both for the mother and the baby. Like other South East Asia countries the prevalence of GDM has also been progressively increasing in Bangladesh. Some population based studies conducted in Bangladesh have revealed an increasing trend of GDM prevalence ranging from 6% to 14% based in using different diagnostic criteria. Aim: To assess the fetal and maternal outcome in pregnancies complicated by gestational diabetes mellitus. Materials and Methods: This cross sectional study was conducted in Combined Military Hospital Dhaka from April 2018 to April 2019. Total 100 cases of GDM admitted in antenatal ward were taken into considerations. Maternal & fetal outcome was studied. Results: Study revealed that gestational diabetes was more common among >25 years old multiparous women. 88% GDM diagnosed at more than 20 weeks of gestation and more than 76% mothers with gestational diabetes delivered by caesarean section, 23% delivered vaginally. Pre-eclampsia were noted in 18% of patients. 25% babies were macrosomic at birth. 12% babies had hyperbillirubanaemia, 10% respiratory distress, 1% had congenital anomalies. Conclusion: Gestational diabetes mellitus is common with a rising prevalence and is associated with higher maternal and neonatal morbidity. It carries additional long term health consequences for the mother and her offspring. Diagnosis and appropriate treatment of the condition decreases morbidities for the mother & baby. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 18-21